Non-Diabetic Renal Disease in Type 2 Diabetic Patients with Nephropathy - Chowdhury, Jubaida Khanam; Hasan, AKM Rashed Ul; Talukder, Rajee Mahmud; Chowdhury, Md Nizamuddin; Islam, Md Nazrul (Journal of Enam Medical College, 2021)
Background: In diabetic patients a good proportion of nephropathy is due to nephropathy other than diabetic renal disease. The detection of superimposed primary nondiabetic renal disease in diabetic patients has an obvious prognostic and therapeutic importance. Objectives: To find out the proportion of diabetic subjects suffering from nondiabetic renal disease (NDRD) and to describe histological varieties in appropriate group. Materials and Methods: This crosssectional study was done in Department of Nephrology, Dhaka Medical College & Hospital, Dhaka from August 2015 to October 2016. Total 37 type 2 diabetic patients were selected. Renal biopsy was done and four cases were excluded due to inadequate sample. Tissue was sent for histopathology and direct immunofluorescence (DIF) examination. On the basis of histological diagnosis of biopsy reports patients were divided into three groups. Group I: Isolated NDRD, Group II: NDRD superimposed on diabetic nephropathy (mixed lesion) and Group III: Isolated diabetic nephropathy (DN). Each patient was evaluated for retinopathy from Ophthalmology department. Based on the presence or absence of retinopathy 33 patients were again divided into two groups. Group A includes patients with diabetic retinopathy (DR) and Group B includes patients without diabetic retinopathy. Results: NDRD was found in 57.6% cases, NDRD plus diabetic nephropathy (DN) in 21.2% and isolated DN in 21.2% cases. In Group A (patients with DR) NDRD, DN and mixed lesion were present in 7 (41.2%), 5 (29.4%) and 5 (29.4%) cases. In Group B (patients without DR) NDRD, DN and mixed lesion were present in 12 (75%), 2 (12.5%) and 2 (12.5%) cases respectively. p value (0.189) was not significant. Conclusion: Kidney disease other than diabetic nephropathy can occur in type 2 diabetic patients. In this study NDRD was found in high frequency. Lack of retinopathy is a poor predictor of nondiabetic kidney disease. Therefore, renal biopsy should be recommended in type 2 diabetic patients with risk factors of NDRD for accurate diagnosis, prompt initiation of disease-specific treatment and ultimately better renal outcome. J Enam Med Col 2020; 10(2): 73-78